Endothelial dysfunction in patients with primary hypertension and hyperhomocysteinemia - Aleksandra Baszczuk (Postępy Higieny i Medycyny Doświadczalnej, 2014)
It is widely accepted that endothelial dysfunction is the basis of the development of cardiovascular diseases, including hypertension. With regard to hypertension, endothelial dysfunction is concerned mainly with impaired vascular expansion; however, it is also related to the intensity of the development of atherosclerosis and thrombosis. Among the factors that cause damage to the endothelium, along with classic risk factors, is hyperhomocysteinemia. Hyperhomocysteinemia promotes the formation of oxygen radicals, lowering the oxidation-reduction potential, adversely affects the biosynthesis and function of vasodilator factors in the vascular wall, contributes to the inhibition of endothelial cell division with intense myocyte proliferation and migration, and impairs production of extracellular matrix components in the vascular wall. In addition, high levels of homocysteine and its derivatives contribute to the modification of LDL and HDL particles, inflammation and disorders in coagulation and fibrinolysis. Biochemical effects of the impact of hyperhomocysteinemia on endothelium can lead to damage of endothelial cells, dysfunction of diastolic function of vessels and reduction of their flexibility through its influence on vascular wall remodeling. These changes lead to an increase in blood pressure, strengthening the development of hypertension and target organ damage in patients with this disease.